Fifth-Order Compact Finite Difference Scheme for Burgers-Huxley Equation - AKKOYUNLU, CANAN (Necip Şimşek, 2025)
The Burgers-Huxley equation arises in several problems in science. The compact finite difference scheme (CFDS) has been developed for the Burgers-Huxley equation. This scheme has been compared different methods for the Burgers-Huxley equation. Dispersive properties are investigated for the linearized equations to examine the nonlinear dynamics after discretisation. The accuracy and computational efficiency of the compact finite differences scheme are shown in numerical test problems.
Keywords: Burgers-huxley Equation; Compact Finite Difference Scheme; Dispersion Analysis